Engineering at Subatomic Scale: Achieving Selective Catalytic Pathways via Tuning of the Oxidation States in Functionalized Single‐Atom Quantum Catalysts. Issue 34 (27th July 2022) - Zeb, Akif; Sahar, Shafaq; Lv, Sheng‐Yao; Yousaf, Ammar Bin; Kasak, Peter; Lin, Xiaoming; Tang, Zhilie; Wu, Yongbo; Li, Guoliang; Xu, An‐Wu
Abstract: Regulating the catalytic pathways of single‐atom sites in single atom catalysts (SACs) is an exciting debate at the moment, which has redirected the research towards understanding and modifying the single‐atom catalytic sites through various strategies including altering the coordination environment of single atom for desirable outcomes as well as increasing their number. One useful aspect concerning the tunability of the catalytic pathways of SACs, which has been overlooked, is the oxidation state dynamics of the single atoms. In this study, iron single‐atoms (FeSA) with variable oxidation states, dependent on the precursors, are harnessed inside a nitrogen‐rich functionalized carbon quantum dots (CQDs) matrix via a facile one‐step and low‐temperature synthesis process. Dynamic electronic properties are imparted to the FeSAs by the simpler carbon dots matrix of CQDs in order to achieve the desired catalytic pathways of reactive oxygen species (ROS) generation in different environments, which are explored experimentally and theoretically for an in‐depth understanding of the redox chemistry that drives the alternative catalytic pathways in FeSA@CQDs. These alternative and oxidation state‐dependent catalytic pathways are employed for specific as well as cascade‐like activities simulating natural enzymes as well as biomarkers for the detection of cancerous cells. Abstract : Alternative catalytic pathways are being regulated in single‐atom catalysts (SACs) by tuning oxidation states of single‐atom metal centers incorporated in nitrogen‐rich 0D carbon quantum dots, dependent on the precursors, via a facile synthesis process. Experimental, mechanistic, and theoretical studies show a controlled catalytic performance in the generation of reactive oxygen species and its further application as single‐atom nanozymes.